GRAMMAR-NAZI ANALYSIS IN ENGLISH LEARNING PROCESS AMONG MILLENIALS IN INDONESIA - Eunike Imanuela Soehendro; Ika Wuri Septiani; Zhafira Zhafarina; Jumanto Jumanto (BASIS (Bahasa dan Sastra Inggris), 2021)
Social media, which was originally used to communicate with other people via online, has begun to be used to exchange knowledge so that it makes it easy for many people to learn more flexibly and without boundaries. Indonesian people are more motivated to learn and practice English through social media, considering that the ability to speak English is a special value when applying to job. However, the main function of social media itself, namely the freedom of expression and opinion, is also an inhibiting factor in learning English. Lots of social media users seem to be less wise in their opinions, especially on grammar issues and do not hesitate to criticize grammatical errors in English posts. The term grammar-nazi is usually attached to these people who tend to correct the grammar. This is the main focus of researchers to conduct grammar-nazi analysis in the process of learning English among millennials in Indonesia which is carried out online. Our research process includes data collection through observation, open coding techniques, axial coding, selective coding, synthesis of results, drawing conclusions, and providing suggestions. Some opinions such as Lauren & Connie (2005) and Mohd Amin et al. (2016) in their research provides an overview of the responses of users who showed a positive with this phenomenon. Meanwhile, research by James E. Carroll (2016) and Sherman & Jaroslav (2014) shows a negative response disagreeing with this phenomenon. The results of this study are expected to be able to provide a sufficient account on grammar-nazi phenomenon in the process of learning English among millennials in Indonesia.